Exploring ethical considerations in machine translation: Addressing bias and cultural sensitivity - Yao, Jinfang; Kasuma, Shaidatul Akma Adi; Al-Hashimy, Hisham Noori Hussain (Journal of Interdisciplinary Studies in Education, 2025)
Through this paper, we aim to explore the ethical considerations related to machine translation, with a focus on eliminating bias and enhancing cultural sensitivity. By considering the experiences of individual participants, we aim to strengthen the ability of algorithms to adapt to diverse cultural environments, thereby contributing to the advancement of machine translation. Using partial least squares (PLS), we analyzed data from 5,000 participants, of whom 178 were specifically selected, to investigate the factors contributing to machine translation bias and overlooked cultural nuances. We explained the key determinants of machine translation bias and proposed solutions. This study provides practical suggestions for designing machine translation systems that are both ethical and culturally sensitive, which will directly affect developers, policymakers, and stakeholders in the translation field. This study employed PLS analysis to offer unique insights into ethical considerations, bias mitigation strategies, cultural sensitivity, and the interrelationships among users in machine translation. By drawing on personal experience, this paper contributes to the growth of machine translation’s popularity.